The Romantic Adventure of Pathfinder: Love Bound to Nature & A Quest of Identity As seen in Cooperâs The Pathfinder or The Inland Sea - Pramono, Edi (Universitas Ahmad Dahlan, 2014)
AbstractÂ Not only does love concern with different sexes of human beings but it also is about God, nature, brotherhood, friendship, and humanity itself. Love does not demand but gives and more it sacrifices for the sake of itself. Pathfinder thus offers a great value of love.Love, despite its universality and immense power embracing human life, might be bound by certain situation and condition as it occurred to Pathfinder. Through an objective approach, this paper tries to put forward how the main character, Pathfinder realized that his love was bound to nature, his nature. The problem emerging from the story concerns the kind of love within the personality of Pathfinder so that he can sincerely encounter, though painfully, his unsuccessful love based on his awareness of his nature.Through a hard effort of easing his own bleeding heart of dealing with the failure in gaining his love, Pathfinder comes to his solution that he has to change his love, from a love of a man towards a woman into a love of a father to his daughter. He has to realize that his nature is different from that of Mabelâs. His age, way of life, customs, neighborhood, and his identity show that he does not match Mabel and so hers to him. His nature calls him back and gives him enlightenment of who he really is. He is neither an Indian nor a white, but he is both an Indian and a white man. That is his accomplishment of his quest on his identity.